Recurrent hydatidiform mole transformed into invasive mole with co-morbid depression- a rare case report - Bhagat, Nisha; Raj, Rajnish (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
The gestational trophoblastic disease is a group of interrelated lesions that arise from abnormal proliferation of placental trophoblast. It comprises of hydatidiform mole (partial or complete), invasive mole, placental site trophoblastic tumor and choriocarcinoma. The occurrence of hydatidiform mole in more than two conceptions is known as recurrent hydatidiform mole. Although, its incidence is less than 2% but it may progress to invasive mole or choriocarcinoma. The case of 26-year old female is reported; she had five consecutive molar pregnancies and the sixth one developed into invasive mole with co-morbid depression that was managed by methotrexate chemotherapy, antidepressant and psychotherapy.